Pengaruh pola asuh orangtua terhadap tingkat kecemasan anak sebelum menjalani perawatan penambalan gigi Di RSGM Unsrat - Sagrang, Patricia S.; Wowor, Vonny N.S.; Mintjelungan, Christy N. (e-GiGi, 2017)
Abstract: One problem of a child behavior that often occurs when they undergo dental treatment is anxiety. There are many factors that can cause anxiety in children, inter alia the style of parenting applied to their children. There are three kinds of parenting, as follows: authoritarian, authoritative, and permissive. This study was aimed to analyze the influence the parenting style upon the child anxiety before dental filling treatment at RSGM Unsrat (dental clinic). This was a descriptive analytical study with a cross sectional design. There were 31 respondents obtained by using purposive sampling method. Data were collected from parenting questionnaires and CFSS-DS (Children Dental Fear Survey Schedule-subscale) and were analyzed by using the Fisher test. The results showed the percentages of parenting, as follows: authoritative parenting 46.87%, authoritarian parenting 34.37%, and permissive parenting 18.76%. Child anxiety levels before dental filling treatment were low-level anxiety 65.62% and moderate-level anxiety 34.38%; high-level anxiety was not found. The Fischer test analyzing the effect of parenting style on anxiety showed a p-value of 0.01. Conclusion: There was a significant effect of parenting style on the child anxiety level before dental filling treatment at RSGM Unsrat.Keywords: parenting styles, anxietyÂ Abstrak: Salah satu sumber masalah pada perilaku yang sering terjadi saat anak menjalani perawatan gigi dan mulut yakni kecemasan. Terdapat banyak faktor yang dapat memengaruhi rasa cemas pada anak, salah satunya ialah gaya pola asuh yang diterapkan orang tua kepada anaknya. Pola asuh terdiri dari 3 macam, yaitu otoriter, demokratis, dan permisif. Penelitian ini bertujuan untuk menganalisis pengaruh pola asuh orang tua terhadap tingkat kecemasan pasien anak sebelum menjalani perawatan penambalan gigi di RSGM Unsrat. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Jumlah sampel sebanyak 32 responden diperoleh dengan purposive sampling. Data dikumpulkan melalui kuesioner pola asuh orangtua dan kuesioner CFSS-DS (Children Fear Survey Schedule-Dental Subscale) dan dianalisis menggunakan uji Fisher. Hasil penelitian mendapatkan pola asuh demokratis sebesar 46,87%, pola asuh otoriter 34,37 %, dan pola asuh permisif 18,76%. Tingkat kecemasan anak sebelum menjalani perawatan penambalan gigi di RSGM Unsrat ialah: tingkat kecemasan rendah 65,62%, tingkat kecemasan sedang 34,38% tidak dijumpai tingkat kecemasan tinggi tidak ada. Analisis data dengan uji Fisher mendapatkan nilai p=0,01. Simpulan: Terdapat pengaruh pola asuh orangtua terhadap tingkat kecemasan anak sebelum menjalani perawatan penambalan gigi di RSGM Unsrat.Kata kunci: pola asuh, tingkat kecemasan